2015
DOI: 10.1063/1.4913691
|View full text |Cite
|
Sign up to set email alerts
|

Widely bandgap tunable amorphous Cd–Ga–O oxide semiconductors exhibiting electron mobilities ≥10 cm2 V−1 s−1

Abstract: Amorphous oxide semiconductors exhibit large electron mobilities; however, their bandgaps are either too large for solar cells or too small for deep ultraviolet applications depending on the materials system. Herein, we demonstrate that amorphous Cd–Ga–O semiconductors display bandgaps covering the entire 2.5–4.3 eV region while maintaining large electron mobilities ≥10 cm2 V−1 s−1. The band alignment diagram obtained by ultraviolet photoemission spectroscopy and the bandgap values reveal that these semiconduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…A broad peak detected at around 22°in every XRD pattern was attributed to the silica glass substrates. The other broad peak observed at around 32°was assigned to a-CGO film, 5) and the intensity of this peak decreased with decreases in C Cd ; a similar dependence was observed in our previous study.…”
Section: Methodssupporting
confidence: 67%
“…A broad peak detected at around 22°in every XRD pattern was attributed to the silica glass substrates. The other broad peak observed at around 32°was assigned to a-CGO film, 5) and the intensity of this peak decreased with decreases in C Cd ; a similar dependence was observed in our previous study.…”
Section: Methodssupporting
confidence: 67%
“…To date, a variety of crystalline transparent conductive oxides (TCOs) have been reported; however, most of them contain the representative TCOs of ZnO, In 2 O 3 , SnO 2 , and Ga 2 O 3 as major constituents. Development of AOSs has followed a similar manner, leading to a-In-Zn-O, a-Zn-Sn-O, a-In-Ga-O, a-In-Sn-Zn-O, a-Sn-Ga-Zn-O, a-Hf-In-Zn-O, a-Ga-Cd-O [1,[8][9][10][11], etc. Among the crystalline TCOs, pure β-Ga 2 O 3 has the largest E g of 4.9 eV [12]; however, electron conduction in pure amorphous Ga 2 O 3 (a-Ga 2 O 3 ) has not yet been reported.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, it is suggested that with increasing Cd ratio (x), CdO grains would be separated out from the In‐Ga‐Cd‐O network and gradually grow up. A similar phenomenon had been reported in other ternary oxide compounds such as In‐Zn‐O, Zn‐Ga‐O, and Cd‐Ga‐O . Additionally, to get more structural information, the average grain size of the InGaCd 6 O sample was calculated using the FWHM of (002) and (111) dominant peaks through the Scherrer's method, featuring an average grain size of ≈37 nm.…”
Section: The Comparison In Performance Of In‐ga‐zn‐o and In‐ga‐cd‐o Tmentioning
confidence: 62%